Respons Tanaman Cabai Besar (Capsicum annuum L.) Terhadap Pemberian Pupuk Organik Hormon Tanaman Unggul - M. A Ralahalu; Meity L Hehanussa; L.L Oszaer (Agrologia, 2013)
This research aimed to study the responses of large chilli plants (Capsicum annuum L.) to treatment with superior plant hormone organic fertilizer and to obtain the optimal concentration of superior plant hormone organic fertilizer on growth and yield of plants. The research was conducted at Gunung Nona, Benteng Village, Nusaniwe Subdistrict, Ambon City, from April to September 2012. The research experiment was arranged in a Completely Randomized Design (CRD) with 3 replications. The experimental factor was the concentration of superior plant hormone organic fertilizer, consisting of P0 = without fertilizer (control),   P1 = 1 ml/l, P2 = 2 ml/l, P3 = 3 ml/l, and P4 = 4 ml/l. The results showed that the concentration of superior plant hormone organic fertilizer influenced significantly on plant growth and yield of large chilli plants, and at a treatment of 3 ml / l  the number of harvested fruit per plant was 70,58 and fruit weight was 241.67 grams